A nano-modified automobile varnish and preparation method thereof
A nano-modified automobile varnish with specific components and preparation methods addresses the issues of antifouling and easy-cleaning, enhancing adhesion and weather resistance, resulting in improved durability and cleaning efficiency.
Patent Information
- Application Number
- CN202410755441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-06-12
AI Technical Summary
Existing automobile varnishes have poor antifouling and easy-cleaning capabilities, leading to reduced adhesion performance, scratch resistance, and weather resistance stability, limiting their use efficiency.
A nano-modified automobile varnish composed of specific raw materials, including acrylic resin, kaolin agent, nano-silica-modified performance regulator, silane coupling agent, film-forming aid, curing agent, and acetone, prepared through a series of treatments enhancing the synergistic effects of these components.
The nano-modified varnish achieves improved easy-cleaning performance, adhesion, scratch resistance, and weathering stability, demonstrating enhanced cleaning ability and durability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile varnish, and in particular to a nano-modified automobile varnish and a preparation method thereof. Background Art
[0002] Existing automobile varnishes have poor antifouling and easy-cleaning capabilities. In order to improve the easy-cleaning performance, the adhesion performance of the product is reduced. At the same time, the product's scratch resistance and weather resistance stability are poor, which limits the product's use efficiency. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide a nano-modified automobile varnish and a preparation method thereof to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a nano-modified automobile varnish, which comprises the following raw materials in parts by weight:
[0006] 40-45 parts of acrylic resin, 8-12 parts of kaolin agent for continuous adjustment, 4-7 parts of nano-silica-modified performance regulator, 4-8 parts of silane coupling agent, 3-5 parts of film-forming aid, 4-7 parts of curing agent, and 30-40 parts of acetone.
[0007] Preferably, the nano-modified automobile varnish comprises the following raw materials in parts by weight:
[0008] 42.5 parts of acrylic resin, 10 parts of kaolin agent for continuous adjustment, 5.5 parts of nano-silica-modified performance regulator, 6 parts of silane coupling agent, 4 parts of film-forming aid, 5.5 parts of curing agent, and 35 parts of acetone.
[0009] Preferably, the solid content of the acrylic resin is 25-30%; the film-forming aid is propylene glycol methyl ether; the curing agent is triethylenetetramine; and the silane coupling agent is silane coupling agent KH560.
[0010] Preferably, the preparation method of the continuously adjusted kaolin agent is:
[0011] S01: irradiate the kaolin with protons for 5 to 10 minutes at a power of 300 W. After the irradiation, heat treat the irradiated kaolin at 135 to 140°C for 5 minutes, and finally cool it to 55°C at a rate of 1 to 2°C / min and keep it warm.
[0012] S02: The insulated kaolin is placed in a sodium lignin sulfonate solution which is 3 to 5 times the total amount of the insulated kaolin, and then a phosphate buffer solution which is 10 to 15% of the total amount of the insulated kaolin and a silicon carbide whisker modifier which is 4 to 7% of the total amount of the insulated kaolin are added, and the mixture is stirred sufficiently to obtain a kaolin solution;
[0013] The preparation method of the silicon carbide whisker modifier is as follows:
[0014] The silicon carbide whisker is immersed in a sufficient amount of yttrium nitrate solution, and then filtered and dried to obtain a silicon carbide whisker impregnating agent;
[0015] A chitosan solution with a mass fraction of 5% was added into a sodium silicate solution with a mass fraction of 10% at a weight ratio of 2:5 and mixed to obtain a chitosan agent;
[0016] The silicon carbide whisker impregnation agent and the chitosan agent are stirred at a weight ratio of 2:3, and after the treatment, the mixture is washed with water and dried to obtain a silicon carbide whisker modifier;
[0017] S03: The continuous adjustment and feeding agent and kaolin liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1000-1500 r / mn for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain the continuous adjustment and feeding kaolin agent.
[0018] Preferably, the mass fraction of the sodium lignin sulfonate solution is 10-15%; the pH value of the phosphate buffer solution is 5.0; and the mass fraction of the yttrium nitrate solution is 2-5%.
[0019] Preferably, the immersion pressure of the immersion treatment is 10-15 MPa, and the immersion time is 20-30 min; the stirring speed of the stirring treatment is 750-850 r / min, and the stirring is 1-2 h.
[0020] Preferably, the preparation method of the continuous adjustment and feeding agent is:
[0021] 4 to 7 parts of hydroxyapatite and 1 to 2 parts of stearic acid are added to 4 to 8 parts of 5% by mass lanthanum chloride solution, and then 1 to 3 parts of sodium dodecylbenzene sulfonate and 2 to 5 parts of sodium alginate are added and blended and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.
[0022] Preferably, the preparation method of the performance modifier based on nano-silicon dioxide modification is:
[0023] S101: mixing the nano-silicon dioxide with a sufficient amount of a 10% by mass potassium permanganate solution, then washing with water and drying to obtain dry nano-silicon dioxide;
[0024] S102: adding 2-5 parts of dry nano-silica and 1-3 parts of glass fiber to 10-15 parts of 8% sodium citrate solution by mass, and then adding 1-3 parts of silane coupling agent KH550, ultrasonically treating, filtering and drying after the treatment, to obtain a performance modifier based on nano-silica modification.
[0025] Preferably, the ultrasonic power of the ultrasonic treatment is 350-450W, and the ultrasonic time is 20-30min.
[0026] The present invention also provides a method for preparing a nano-modified automobile varnish, comprising the following steps:
[0027] The nano-modified automobile varnish of the present invention can be obtained by uniformly mixing acrylic resin, kaolin agent, nano-silicon dioxide-modified synergist, silane coupling agent, film-forming aid, curing agent and acetone raw materials according to a proportion.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The nano-modified automobile varnish of the present invention adopts acrylic resin as a matrix, adds a silane coupling agent, a film-forming aid, and a curing agent as functional additives, and simultaneously adds a kaolin agent and a nano-silicon dioxide-modified performance-adjusting agent, and the two are coordinated and synergistically effective to obtain an automobile varnish product with excellent easy-cleaning performance and significant adhesion performance of the product, and the easy-cleaning performance and adhesion performance are coordinated and improved, and the product has significant scratch resistance and weathering stability effects;
[0030] The kaolin agent used in the continuous adjustment is first proton irradiated for 5 to 10 minutes with an irradiation power of 300W. After the irradiation, the irradiated kaolin is heat treated at 135 to 140°C for 5 minutes, and finally cooled to 55°C at a rate of 1 to 2°C / min, and kept warm. The active efficiency of kaolin is optimized through proton irradiation and thermal improvement, and then sodium lignin sulfonate solution, phosphate buffer solution and silicon carbide whisker modifier are jointly prepared. The silicon carbide whisker modifier is treated by immersing whiskers in yttrium nitrate solution to obtain yttrium-doped silicon carbide whiskers, and then chitosan solution and sodium silicate solution are combined to prepare the kaolin agent. The mixed chitosan agent is stirred, improved by silicon carbide whiskers, and then combined with kaolin raw materials and distributed in the system to enhance the bonding performance between the product and the base layer, while improving the cleaning points and improving the cleanliness. Hydroxyapatite, stearic acid, lanthanum chloride solution, sodium dodecylbenzene sulfonate and sodium alginate are blended and ball-milled. Through the coordinated blending treatment between the raw materials, the raw materials are coordinated and synergistic with each other, and the obtained continuous adjustment and continuous feeding agent is further coordinated and synergistic with the kaolin liquid, so that the cleaning performance and adhesion performance of the product are enhanced, and the weather resistance and scratch resistance stability of the product are further enhanced;
[0031] The performance-enhancing agent modified by nano-silica is prepared by treating nano-silica with potassium permanganate solution to optimize its activity and dispersion, and then ultrasonically treating the glass fiber, sodium citrate solution and silane coupling agent KH550. The glass fiber and nano-silica are blended and coordinated to strengthen the system structure, and the synergistic effect of the performance-enhancing agent modified by nano-silica and the continuously adjusted kaolin agent is enhanced, and the performance of the product is further improved. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] A nano-modified automobile varnish of this embodiment includes the following raw materials in parts by weight:
[0034] 40-45 parts of acrylic resin, 8-12 parts of kaolin agent for continuous adjustment, 4-7 parts of nano-silica-modified performance regulator, 4-8 parts of silane coupling agent, 3-5 parts of film-forming aid, 4-7 parts of curing agent, and 30-40 parts of acetone.
[0035] The nano-modified automobile varnish of this embodiment comprises the following raw materials in parts by weight:
[0036] 42.5 parts of acrylic resin, 10 parts of kaolin agent for continuous adjustment, 5.5 parts of nano-silica-modified performance regulator, 6 parts of silane coupling agent, 4 parts of film-forming aid, 5.5 parts of curing agent, and 35 parts of acetone.
[0037] The solid content of the acrylic resin in this embodiment is 25-30%; the film-forming aid is propylene glycol methyl ether; the curing agent is triethylenetetramine; and the silane coupling agent is silane coupling agent KH560.
[0038] The preparation method of the continuous adjustment and continuous feeding kaolin agent of this embodiment is:
[0039] S01: irradiate the kaolin with protons for 5 to 10 minutes at a power of 300 W. After the irradiation, heat treat the irradiated kaolin at 135 to 140°C for 5 minutes, and finally cool it to 55°C at a rate of 1 to 2°C / min and keep it warm.
[0040] S02: The insulated kaolin is placed in a sodium lignin sulfonate solution which is 3 to 5 times the total amount of the insulated kaolin, and then a phosphate buffer solution which is 10 to 15% of the total amount of the insulated kaolin and a silicon carbide whisker modifier which is 4 to 7% of the total amount of the insulated kaolin are added, and the mixture is stirred sufficiently to obtain a kaolin solution;
[0041] The preparation method of the silicon carbide whisker modifier is as follows:
[0042] The silicon carbide whisker is immersed in a sufficient amount of yttrium nitrate solution, and then filtered and dried to obtain a silicon carbide whisker impregnating agent;
[0043] A chitosan solution with a mass fraction of 5% was added into a sodium silicate solution with a mass fraction of 10% at a weight ratio of 2:5 and mixed to obtain a chitosan agent;
[0044] The silicon carbide whisker impregnation agent and the chitosan agent are stirred at a weight ratio of 2:3, and after the treatment, the mixture is washed with water and dried to obtain a silicon carbide whisker modifier;
[0045] S03: The continuous adjustment and feeding agent and kaolin liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1000-1500 r / mn for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain the continuous adjustment and feeding kaolin agent.
[0046] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 10-15%; the pH value of the phosphate buffer solution is 5.0; and the mass fraction of the yttrium nitrate solution is 2-5%.
[0047] The immersion pressure of the immersion treatment in this embodiment is 10-15 MPa, and the immersion time is 20-30 min; the stirring speed of the stirring treatment is 750-850 r / min, and the stirring is 1-2 h.
[0048] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:
[0049] 4 to 7 parts of hydroxyapatite and 1 to 2 parts of stearic acid are added to 4 to 8 parts of 5% by mass lanthanum chloride solution, and then 1 to 3 parts of sodium dodecylbenzene sulfonate and 2 to 5 parts of sodium alginate are added and blended and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.
[0050] The preparation method of the performance-regulating agent based on nano-silicon dioxide modification in this embodiment is as follows:
[0051] S101: mixing the nano-silicon dioxide with a sufficient amount of a 10% by mass potassium permanganate solution, then washing with water and drying to obtain dry nano-silicon dioxide;
[0052] S102: adding 2-5 parts of dry nano-silica and 1-3 parts of glass fiber to 10-15 parts of 8% sodium citrate solution by mass, and then adding 1-3 parts of silane coupling agent KH550, ultrasonically treating, filtering and drying after the treatment, to obtain a performance modifier based on nano-silica modification.
[0053] The ultrasonic power of the ultrasonic treatment in this embodiment is 350-450W, and the ultrasonic time is 20-30min.
[0054] A method for preparing a nano-modified automobile varnish of the present embodiment comprises the following steps:
[0055] The nano-modified automobile varnish of the present invention can be obtained by uniformly mixing acrylic resin, kaolin agent, nano-silicon dioxide-modified synergist, silane coupling agent, film-forming aid, curing agent and acetone raw materials according to a proportion.
[0056] Example 1
[0057] A nano-modified automobile varnish of this embodiment includes the following raw materials in parts by weight:
[0058] 40 parts of acrylic resin, 8 parts of kaolin agent for continuous adjustment, 4 parts of nano-silica-modified performance regulator, 4 parts of silane coupling agent, 3 parts of film-forming aid, 4 parts of curing agent, and 30 parts of acetone.
[0059] The solid content of the acrylic resin in this embodiment is 25%; the film-forming aid is propylene glycol methyl ether; the curing agent is triethylenetetramine; and the silane coupling agent is silane coupling agent KH560.
[0060] The preparation method of the continuous adjustment and continuous feeding kaolin agent of this embodiment is:
[0061] S01: The kaolin was first proton irradiated for 5 min at a power of 300 W. After the irradiation, the irradiated kaolin was heat treated at 135 °C for 5 min, and finally cooled to 55 °C at a rate of 1 °C / min and kept warm;
[0062] S02: The insulated kaolin is placed in a sodium lignin sulfonate solution which is 3 times the total amount of the insulated kaolin, and then a phosphate buffer solution which is 10% of the total amount of the insulated kaolin and a silicon carbide whisker modifier which is 4% of the total amount of the insulated kaolin are added, and the mixture is stirred sufficiently to obtain a kaolin solution;
[0063] The preparation method of the silicon carbide whisker modifier is as follows:
[0064] The silicon carbide whisker is immersed in a sufficient amount of yttrium nitrate solution, and then filtered and dried to obtain a silicon carbide whisker impregnant;
[0065] A chitosan solution with a mass fraction of 5% was added into a sodium silicate solution with a mass fraction of 10% at a weight ratio of 2:5 and mixed to obtain a chitosan agent;
[0066] The silicon carbide whisker impregnation agent and the chitosan agent are stirred at a weight ratio of 2:3, and after the treatment, the mixture is washed with water and dried to obtain a silicon carbide whisker modifier;
[0067] S03: The continuous adjustment and feeding agent and kaolin liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1000 r / mn for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the continuous adjustment and feeding kaolin agent.
[0068] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 10%; the pH value of the phosphate buffer solution is 5.0; and the mass fraction of the yttrium nitrate solution is 2%.
[0069] The immersion pressure of the immersion treatment in this embodiment is 10 MPa, and the immersion time is 20 min; the stirring speed of the stirring treatment is 750 r / min, and the stirring is 1 hour.
[0070] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:
[0071] 4 parts of hydroxyapatite and 1 part of stearic acid are added to 4 parts of 5% by mass lanthanum chloride solution, and then 1 part of sodium dodecylbenzene sulfonate and 2 parts of sodium alginate are added and blended and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous conditioning and continuous feeding agent.
[0072] The preparation method of the performance-regulating agent based on nano-silicon dioxide modification in this embodiment is as follows:
[0073] S101: mixing the nano-silicon dioxide with a sufficient amount of a 10% by mass potassium permanganate solution, then washing with water and drying to obtain dry nano-silicon dioxide;
[0074] S102: adding 2 parts of dry nano-silica and 1 part of glass fiber to 10 parts of 8% sodium citrate solution by mass, and then adding 1 part of silane coupling agent KH550, ultrasonically treating, filtering and drying after the treatment, to obtain a performance modifier modified by nano-silica.
[0075] The ultrasonic power of the ultrasonic treatment in this embodiment is 350W, and the ultrasonic time is 20min.
[0076] A method for preparing a nano-modified automobile varnish of the present embodiment comprises the following steps:
[0077] The nano-modified automobile varnish of the present invention can be obtained by uniformly mixing acrylic resin, kaolin agent, nano-silicon dioxide-modified synergist, silane coupling agent, film-forming aid, curing agent and acetone raw materials according to a proportion.
[0078] Example 2
[0079] A nano-modified automobile varnish of this embodiment includes the following raw materials in parts by weight:
[0080] 45 parts of acrylic resin, 12 parts of kaolin agent for continuous adjustment, 7 parts of nano-silica-modified performance regulator, 8 parts of silane coupling agent, 5 parts of film-forming aid, 7 parts of curing agent, and 40 parts of acetone.
[0081] The solid content of the acrylic resin in this embodiment is 30%; the film-forming aid is propylene glycol methyl ether; the curing agent is triethylenetetramine; and the silane coupling agent is silane coupling agent KH560.
[0082] The preparation method of the continuous adjustment and continuous feeding kaolin agent of this embodiment is:
[0083] S01: The kaolin was first proton irradiated for 10 min at a power of 300 W. After the irradiation, the irradiated kaolin was heat treated at 140 °C for 5 min, and finally cooled to 55 °C at a rate of 2 °C / min and kept warm.
[0084] S02: The insulated kaolin is placed in a sodium lignin sulfonate solution of 5 times the total amount of the insulated kaolin, and then a phosphate buffer solution of 15% of the total amount of the insulated kaolin and a silicon carbide whisker modifier of 7% of the total amount of the insulated kaolin are added, and the mixture is stirred sufficiently to obtain a kaolin solution;
[0085] The preparation method of the silicon carbide whisker modifier is as follows:
[0086] The silicon carbide whisker is immersed in a sufficient amount of yttrium nitrate solution, and then filtered and dried to obtain a silicon carbide whisker impregnating agent;
[0087] A chitosan solution with a mass fraction of 5% was added into a sodium silicate solution with a mass fraction of 10% at a weight ratio of 2:5 and mixed to obtain a chitosan agent;
[0088] The silicon carbide whisker impregnation agent and the chitosan agent are stirred at a weight ratio of 2:3, and after the treatment, the mixture is washed with water and dried to obtain a silicon carbide whisker modifier;
[0089] S03: The continuous adjustment and feeding agent and kaolin liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1500r / mn for 2h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the continuous adjustment and feeding kaolin agent.
[0090] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 15%; the pH value of the phosphate buffer solution is 5.0; and the mass fraction of the yttrium nitrate solution is 5%.
[0091] The immersion pressure of the immersion treatment in this embodiment is 15 MPa, and the immersion time is 30 min; the stirring speed of the stirring treatment is 850 r / min, and the stirring is 2 h.
[0092] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:
[0093] 7 parts of hydroxyapatite and 2 parts of stearic acid are added to 8 parts of 5% by mass lanthanum chloride solution, and then 3 parts of sodium dodecylbenzene sulfonate and 5 parts of sodium alginate are added and blended and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.
[0094] The preparation method of the performance-regulating agent based on nano-silicon dioxide modification in this embodiment is as follows:
[0095] S101: mixing the nano-silicon dioxide with a sufficient amount of a 10% by mass potassium permanganate solution, then washing with water and drying to obtain dry nano-silicon dioxide;
[0096] S102: adding 5 parts of dry nano-silica and 3 parts of glass fiber to 15 parts of 8% sodium citrate solution by mass, and then adding 3 parts of silane coupling agent KH550, ultrasonically treating, filtering and drying after the treatment, to obtain a performance modifier modified by nano-silica.
[0097] The ultrasonic power of the ultrasonic treatment in this embodiment is 450W, and the ultrasonic time is 30min.
[0098] A method for preparing a nano-modified automobile varnish of the present embodiment comprises the following steps:
[0099] The nano-modified automobile varnish of the present invention can be obtained by uniformly mixing acrylic resin, kaolin agent, nano-silicon dioxide-modified synergist, silane coupling agent, film-forming aid, curing agent and acetone raw materials according to a proportion.
[0100] Example 3
[0101] A nano-modified automobile varnish of this embodiment includes the following raw materials in parts by weight:
[0102] 42.5 parts of acrylic resin, 10 parts of kaolin agent for continuous adjustment, 5.5 parts of nano-silica-modified performance regulator, 6 parts of silane coupling agent, 4 parts of film-forming aid, 5.5 parts of curing agent, and 35 parts of acetone.
[0103] The solid content of the acrylic resin in this embodiment is 27.5%; the film-forming aid is propylene glycol methyl ether; the curing agent is triethylenetetramine; and the silane coupling agent is silane coupling agent KH560.
[0104] The preparation method of the continuous adjustment and continuous feeding kaolin agent of this embodiment is:
[0105] S01: The kaolin was first proton irradiated for 7.5 min at a power of 300 W. After the irradiation, the irradiated kaolin was heat treated at 137 °C for 5 min, and finally cooled to 55 °C at a rate of 1.5 °C / min and kept warm.
[0106] S02: The insulated kaolin is placed in a sodium lignin sulfonate solution of 4 times the total amount of the insulated kaolin, and then a phosphate buffer solution of 12.5% of the total amount of the insulated kaolin and a silicon carbide whisker modifier of 5.5% of the total amount of the insulated kaolin are added, and the mixture is stirred sufficiently to obtain a kaolin solution;
[0107] The preparation method of the silicon carbide whisker modifier is as follows:
[0108] The silicon carbide whisker is immersed in a sufficient amount of yttrium nitrate solution, and then filtered and dried to obtain a silicon carbide whisker impregnating agent;
[0109] A chitosan solution with a mass fraction of 5% was added into a sodium silicate solution with a mass fraction of 10% at a weight ratio of 2:5 and mixed to obtain a chitosan agent;
[0110] The silicon carbide whisker impregnation agent and the chitosan agent are stirred at a weight ratio of 2:3, and after the treatment, the mixture is washed with water and dried to obtain a silicon carbide whisker modifier;
[0111] S03: The continuous adjustment and feeding agent and kaolin liquid are mixed in a weight ratio of 3:5 and ball-milled at a ball-milling speed of 1250 r / mn for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the continuous adjustment and feeding kaolin agent.
[0112] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 12.5%; the pH value of the phosphate buffer solution is 5.0; and the mass fraction of the yttrium nitrate solution is 3.5%.
[0113] The immersion pressure of the immersion treatment in this embodiment is 12.5 MPa, and the immersion time is 25 min; the stirring speed of the stirring treatment is 800 r / min, and the stirring time is 1.5 h.
[0114] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:
[0115] 5.5 parts of hydroxyapatite and 1.5 parts of stearic acid are added to 6 parts of 5% by mass lanthanum chloride solution, and then 2 parts of sodium dodecylbenzene sulfonate and 3.5 parts of sodium alginate are added and blended and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.
[0116] The preparation method of the performance-regulating agent based on nano-silicon dioxide modification in this embodiment is as follows:
[0117] S101: mixing the nano-silicon dioxide with a sufficient amount of a 10% by mass potassium permanganate solution, then washing with water and drying to obtain dry nano-silicon dioxide;
[0118] S102: adding 3.5 parts of dry nano-silica and 2 parts of glass fiber to 12.5 parts of 8% sodium citrate solution, and then adding 2 parts of silane coupling agent KH550, ultrasonically treating, filtering and drying after the treatment, to obtain a performance modifier based on nano-silica modification.
[0119] The ultrasonic power of the ultrasonic treatment in this embodiment is 400 W, and the ultrasonic time is 25 min.
[0120] A method for preparing a nano-modified automobile varnish of the present embodiment comprises the following steps:
[0121] The nano-modified automobile varnish of the present invention can be obtained by uniformly mixing acrylic resin, kaolin agent, nano-silicon dioxide-modified synergist, silane coupling agent, film-forming aid, curing agent and acetone raw materials according to a proportion.
[0122] Comparative Example 1
[0123] The difference from Example 3 is that no kaolin agent is added for continuous adjustment.
[0124] Comparative Example 2
[0125] The difference from Example 3 is that no silicon carbide whisker modifier is added in the preparation of the continuously adjusted kaolin agent.
[0126] Comparative Example 3
[0127] The difference from Example 3 is that chitosan agent treatment is not used in the preparation of the silicon carbide whisker modifier.
[0128] Comparative Example 4
[0129] The difference from Example 3 is that the yttrium nitrate solution immersion treatment is not used in the preparation of the silicon carbide whisker modifier.
[0130] Comparative Example 5
[0131] The difference from Example 3 is that the continuous adjustment and continuous feeding agent treatment was not used in the preparation of the continuous adjustment and continuous feeding kaolin agent.
[0132] Comparative Example 6
[0133] The difference from Example 3 is that acetone is used instead of lanthanum chloride solution in the preparation of the continuous adjustment and feeding agent, and sodium alginate is not added.
[0134] Comparative Example 7
[0135] The difference from Example 3 is that the preparation method of the continuous adjustment and continuous feeding agent is different. 1.5 parts of stearic acid are added to 6 parts of 5% by mass lanthanum chloride solution, and then 2 parts of sodium dodecylbenzene sulfonate are added and mixed to obtain the continuous adjustment and continuous feeding agent.
[0136] Comparative Example 8
[0137] The difference from Example 3 is that no performance-enhancing agent based on nano-silicon dioxide modification is added.
[0138] Comparative Example 9
[0139] The difference from Example 3 is that the performance-enhancing agent modified with nano-silicon dioxide is not processed in step S102.
[0140] Comparative Example 10
[0141] The difference from Example 3 is that glass fiber and silane coupling agent KH550 are not added in the S102 treatment.
[0142] The performance of the products of Examples 1-3 and Comparative Examples 1-10 was tested under normal conditions. Oil stains were applied to the test products and dried. The cleaning ability of the products was reflected by testing the wiping force of the oil stains. At the same time, according to GB / T1865-1997 "Artificial Weathering and Artificial Radiation Exposure of Paints and Varnishes", after 1000 hours of artificial weathering, the products were wiped 20 times with a scratching force of 10N. The weather resistance and scratch stability of the products were tested. The test results are as follows;
[0143]
[0144]
[0145] It is concluded from Examples 1-3 and Comparative Examples 1-10 that
[0146] The product of Example 3 of the present invention can achieve coordinated improvement in cleaning ability and substrate bonding performance under normal conditions, and the product has significant performance stability under weather resistance and scratch resistance conditions;
[0147] The product does not contain kaolin agent or one of the performance-enhancing agents modified by nano-silicon dioxide, and the performance of the product deteriorates significantly. The synergistic effect of the two agents is the most obvious.
[0148] The performance of the products tended to deteriorate when the silicon carbide whisker modifier was not added to the kaolin agent, the silicon carbide whisker modifier was not treated with chitosan agent, and the silicon carbide whisker modifier was not treated with yttrium nitrate solution immersion.
[0149] At the same time, the continuous adjustment and continuous advancement agent treatment was not used in the preparation of the continuous adjustment and continuous advancement kaolin agent, acetone was used to replace the lanthanum chloride solution in the preparation of the continuous adjustment and continuous advancement agent, and sodium alginate was not added. The preparation method of the continuous adjustment and continuous advancement agent was different. 1.5 parts of stearic acid were added to 6 parts of 5% by mass lanthanum chloride solution, and then 2 parts of sodium dodecylbenzene sulfonate were added to fully blend to obtain the continuous adjustment and continuous advancement agent. The performance of the products showed a trend of deterioration. Only the silicon carbide whisker modifier, the continuous adjustment and continuous advancement agent obtained by the method of the present invention and the continuous adjustment and continuous advancement kaolin agent obtained by the specific process of the present invention had the most significant performance effect of the product, and the use of other methods instead was not as obvious as the effect of the present invention;
[0150] The performance-regulating agent modified with nano-silica was not processed by step S102, and glass fiber and silane coupling agent KH550 were not added in the S102 process. The performance of the product also showed a trend of deterioration. Only the performance-regulating agent modified with nano-silica obtained by the S102 process obtained by the specific process of the present invention had the most significant performance effect. Other methods were not as obvious as the effect of the present invention.
[0151] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0152] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A nano-modified automobile varnish, characterized in that: The automobile clear coat comprises the following raw materials in parts by weight: 40-45 parts of acrylic resin, 8-12 parts of kaolin agent for continuous mixing, 4-7 parts of nano-silica modified synergist, 4-8 parts of silane coupling agent, 3-5 parts of film-forming aid, 4-7 parts of curing agent, 30-40 parts of acetone; The preparation method of the continuously adjusted kaolin agent is as follows: S01: irradiate the kaolin with protons for 5 to 10 minutes at a power of 300 W. After the irradiation, heat treat the irradiated kaolin at 135 to 140°C for 5 minutes, and finally cool it to 55°C at a rate of 1 to 2°C / min and keep it warm. S02: The insulated kaolin is placed in a sodium lignin sulfonate solution which is 3 to 5 times the total amount of the insulated kaolin, and then a phosphate buffer solution which is 10 to 15% of the total amount of the insulated kaolin and a silicon carbide whisker modifier which is 4 to 7% of the total amount of the insulated kaolin are added, and the mixture is stirred sufficiently to obtain a kaolin solution; The preparation method of the silicon carbide whisker modifier is as follows: The silicon carbide whisker is immersed in a sufficient amount of yttrium nitrate solution, and then filtered and dried to obtain a silicon carbide whisker impregnating agent; A chitosan solution with a mass fraction of 5% was added into a sodium silicate solution with a mass fraction of 10% at a weight ratio of 2:5 and mixed to obtain a chitosan agent; The silicon carbide whisker impregnation agent and the chitosan agent are stirred at a weight ratio of 2:3, and after the treatment, the mixture is washed with water and dried to obtain a silicon carbide whisker modifier; S03: mixing the continuous adjustment and continuous feeding agent and the kaolin liquid in a weight ratio of 3:5 and subjecting them to ball milling at a ball milling speed of 1000-1500 r / min for 2 h. After the ball milling is completed, washing and drying are performed to obtain the continuous adjustment and continuous feeding kaolin agent; The preparation method of the continuous adjustment and continuous feeding agent is: 4-7 parts of hydroxyapatite and 1-2 parts of stearic acid are added to 4-8 parts of 5% by mass lanthanum chloride solution, and then 1-3 parts of sodium dodecylbenzene sulfonate and 2-5 parts of sodium alginate are added and mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous conditioning and continuous feeding agent; The preparation method of the performance modifier based on nano-silicon dioxide modification is as follows: S101: mixing the nano-silicon dioxide with a sufficient amount of a 10% by mass potassium permanganate solution, then washing with water and drying to obtain dry nano-silicon dioxide; S102: Add 2-5 parts of dry nano-silica and 1-3 parts of glass fiber to 10-15 parts of 8% sodium citrate solution by mass, then add 1-3 parts of silane coupling agent KH550, ultrasonically treat, filter and dry after the treatment, to obtain a performance modifier modified by nano-silica.
2. A nano-modified automobile varnish according to claim 1, characterized in that: The nano-modified automobile varnish comprises the following raw materials in parts by weight: 42.5 parts of acrylic resin, 10 parts of kaolin agent for continuous adjustment, 5.5 parts of nano-silica-modified performance regulator, 6 parts of silane coupling agent, 4 parts of film-forming aid, 5.5 parts of curing agent, and 35 parts of acetone.
3. A nano-modified automobile varnish according to claim 1, characterized in that: The solid content of the acrylic resin is 25-30%; the film-forming aid is propylene glycol methyl ether; the curing agent is triethylenetetramine; and the silane coupling agent is silane coupling agent KH560.
4. A nano-modified automobile varnish according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 10-15%; the pH value of the phosphate buffer solution is 5.0; and the mass fraction of the yttrium nitrate solution is 2-5%.
5. A nano-modified automobile varnish according to claim 1, characterized in that: The immersion pressure of the immersion treatment is 10-15 MPa, and the immersion time is 20-30 min; the stirring speed of the stirring treatment is 750-850 r / min, and the stirring is 1-2 h.
6. A nano-modified automobile varnish according to claim 1, characterized in that: The ultrasonic power of the ultrasonic treatment is 350-450W, and the ultrasonic time is 20-30min.
7. A method for preparing a nano-modified automobile varnish according to any one of claims 1 to 6, characterized in that: The following steps are involved: The acrylic resin, the kaolin agent, the nano-silica modified synergist, the silane coupling agent, the film-forming aid, the curing agent and the acetone raw material are mixed evenly according to the proportion to obtain the nano-modified automobile varnish.
Citation Information
Patent Citations
Polyimide high-temperature-resistant paint for new energy electromagnetic wire and preparation method of polyimide high-temperature-resistant paint
CN117551387A
High-temperature-resistant heat-conducting insulating paint and preparation method thereof
CN117925055A
